A smart soft actuator using a single shape memory alloy for twisting actuation. (12th November 2015) - Shim, Jae-Eul; Quan, Ying-Jun; Wang, Wei; Rodrigue, Hugo; Song, Sung-Hyuk; Ahn, Sung-Hoon
Abstract: Recently, robots have become a topic of interest with regard to their functionality as they need to complete a large number of diverse tasks in a variety of environments. When using traditional mechanical components, many parts are needed to realize complex deformations, such as motors, hinges, and cranks. To produce complex deformations, this work introduces a smart soft composite torsional actuator using a single shape memory alloy (SMA) wire without any additional elements. The proposed twisting actuator is composed of a torsionally prestrained SMA wire embedded at the center of a polydimethylsiloxane matrix that twists by applying an electric current upon joule heating of the SMA wire. This report shows the actuator design, fabrication method, and results for the twisting angle and actuation moment. Results show that a higher electric current helps reach the maximum twisting angle faster, but that if the current is too low or too high, it will not be able to reach its maximum deformation. Also, both the twisting angle and the twisting moment increase with a large applied twisting prestrain, but this increase has an asymptotic behavior. However, results for both the width and the thickness of the actuator show that a larger width and thickness reduce the maximum actuation angle of the actuator. This paper also presents a new mechanism for an SMA-actuated active catheter using only two SMA wires with a total length of 170 mm to bend the tip of the catheter in multiple directions. The fabricated active catheter's maximum twisting angle is 270°, and the maximum bending curvature is 0.02 mm −1 .